Evaluation of a manual-based training program in changing auxiliary nurse midwives (ANMs) knowledge, attitudes, and skills related to maternal mental health - Vijayalakshmi Poreddi; Sailaxmi Gandhi; Ramachandra; Sundarnag Ganjekar; Geetha Desai; Prabha S.Chandra (Indian Journal of Psychiatry, 2023)
This study evaluates the effectiveness of a manual-based training program in improving auxiliary nurse midwives (ANMs) knowledge, attitudes, and skills related to maternal mental health.
Keywords: Public health; Internal medicine; Epidemiology